Psychological flexibility as a potential change factor in cognitive behavioural therapy of OCD. Issue 4 (4th July 2022) - Schubert, Christiane; Hilbert, Sven; Favreau, Matthias; Wolstein, Jörg; Voderholzer, Ulrich
Abstract: Background: To gain a better understanding about which aspects of the treatment work for obsessive-compulsive disorders (OCD), the investigation of possible change factors is essential. Psychological flexibility (PsyF) has been of interest in research on successful OCD therapy for some time. Exposure interventions and cognitive strategies in cognitive behavioural therapy (CBT) for OCD may enhance PsyF. To date, however, no process studies have been published that clarify the role of PsyF as a possible change factor for the reduction of OCD symptoms. Aims: This study investigates whether PsyF works as a mediator in successful CBT treatment of OCD. Method: The study recruited 112 adults diagnosed with OCD in a multi-modal in-patient treatment with specific CBT including exposure and response prevention (ERP). The Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) was used to measure OCD symptoms and three self-constructed items to assess PsyF. PsyF was conceptualised as the capability of patients to accept stressful feelings and thoughts. Data were collected weekly. For statistical analysis at the process level, longitudinal multi-level models (MLMs) with random intercepts and linear growth curves were estimated to test for mediation of PsyF on Y-BOCS. Results: OCD symptoms decreased significantly and PsyF increased in patients throughout the course of therapy. MLM revealed that higher average values in PsyF were associated with lower Y-BOCS sum values, but only values between subjects significantly predicted the degree of obsessions and compulsions. Conclusions: Although research shows that PsyF is enhanced by CBT and also shows a connection with Y-BOCS values, its role as a mediator could not be confirmed.